Returning Young Mexican Farmers to the Land - de Dinechin, Frederic (World Bank, Washington, DC, 2012)
This note recounts that by the early 2000s, the Government of Mexico and the Secretariat of Agrarian Reform, in particular, had come to see investment in "the more dynamic young segment of the population endowed with more human capital" as the key to revitalizing the moribund rural economy of the country's social sector. Approaching this objective programmatically would entail establishing a land fund from which to lend to young farmers, and creating effective incentives for older landholders to transfer their land. Careful analysis would be required, including examination of social welfare schemes, to assure that senior landholders who transfer their land to younger counterparts could do so without relinquishing their security. By 2006, the program had been deemed a success and had become an example for all of Mexico.